2014
DOI: 10.1158/1078-0432.ccr-13-2750
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-31-3p Expression Is Linked to Progression-free Survival in Patients with KRAS Wild-type Metastatic Colorectal Cancer Treated with Anti-EGFR Therapy

Abstract: Purpose: To identify microRNAs (miRNA) that predict response to anti-EGFR antibodies in patients with wild-type KRAS metastatic colorectal cancer (mCRC).Experimental Design: miRNA profiling was performed in a training set of 87 patients with mCRC refractory to chemotherapy treated with anti-EGFR antibodies. This included 33 fresh-frozen (FF) and 35 formalin-fixed paraffin-embedded (FFPE) samples retrospectively collected and 19 prospectively collected FF samples. An independent validation cohort consisting of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 46 publications
4
55
2
Order By: Relevance
“…In contrast, it is also reported to be down-regulated in cancer and prevent metastasis in cancer cells12. Like miR-31, expression of miR-31* is also up-regulated in cancer and two pre-cancer tissues in this study like a report in another study13, but its expression was found to be significantly associated with progression free survival of metastatic colorectal cancer14. MiR-7 is a known OncomiR and its expression was up-regulated in cancer, leukoplakia and lichen planus tissues in this study, like in different cancers from other report15.…”
Section: Discussionsupporting
confidence: 58%
“…In contrast, it is also reported to be down-regulated in cancer and prevent metastasis in cancer cells12. Like miR-31, expression of miR-31* is also up-regulated in cancer and two pre-cancer tissues in this study like a report in another study13, but its expression was found to be significantly associated with progression free survival of metastatic colorectal cancer14. MiR-7 is a known OncomiR and its expression was up-regulated in cancer, leukoplakia and lichen planus tissues in this study, like in different cancers from other report15.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, both expression and methylation levels of miR-148a are linked with lack of response to 5-FU and oxaliplatin chemotherapies in advanced CRC patients 273 . A recent comprehensive array-based interrogation of tumor tissues collected from KRAS wild-type metastatic CRC (mCRC) patients treated with anti-EGFR therapy identified miR-31-3p as a negative predictor of progression free survival (PFS) 274 .…”
Section: Noncoding Rnasmentioning
confidence: 99%
“…Interestingly, microRNA-31 has been shown to activate RAS signaling by repressing RAS p21 GTPase activating protein 1 [44]. More evidence for the involvement of miR-31-3p in RAS signaling and EGFR inhibitor resistance came from a number of other studies, which make this microRNA a potential biomarker for future evaluation in prospective clinical trials [45,46,47,48]. Though we did not detect increased apoptosis activation in our cell models, there have been some reports about the pro-apoptotic effect of sorafenib in liver cancer in in vivo models [49].…”
Section: Discussionmentioning
confidence: 99%